Organizational Capital and Financial Performance; What is the Mediation Effect of Firm Innovation: Evidence from Insurance Firms in Kenya - Kirwa, Tecla; Ngeno, Vincent (Journal of Accounting, Business and Finance Research, 2020)
Purpose: following the Resource Based View Theory, this study explored whether firm innovation mediated the upshot of organization capital on firm performance in Kenyan insurance firms. Design / Methodology: the research surveyed 49 insurance firms in Kenya using explanatory research design. The hypotheses testing used Structural Equation Modelling. Findings: The outcome revealed that organization capital positively influences firm innovativeness and that firm innovation partially arbitrates the association between organization capital and performance of the firm. Practical implication: the outcome of the research suggested that for insurance firms to be innovative organization capital should be enhanced in terms of availability in the systems, databases, files, licenses or patents which is termed very important for implementation of innovation since such knowledge is the result of humdrum routine of employees, reminds usage process, flexible in usage for new contexts and more significantly it improves employees technology skills thus resulting to a better performance by the firm.